Analisis Faktor Risiko Penyakit Tidak Menular pada Masyarakat Kota Mataram - Zayn Ibrahim; Ahmad Idham (Lembaga Penelitian dan Pendidikan, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and cardiovascular diseases have shown an increasing prevalence in urban areas, including Mataram City. This study aims to analyze the risk factors contributing to the occurrence of NCDs among the population of Mataram City. An analytical cross-sectional design was employed with respondents aged ≥18 years selected through stratified random sampling. Data were collected using a structured questionnaire, anthropometric measurements, and blood pressure as well as blood glucose examinations. Logistic regression analysis was performed to identify the associations between risk factors (dietary patterns, physical activity, smoking habits, alcohol consumption, and body mass index) and the occurrence of NCDs. The results showed that high-fat dietary patterns (OR=2.15; 95%CI:1.34–3.44), low physical activity (OR=1.87; 95%CI:1.21–2.90), smoking habits (OR=1.65; 95%CI:1.10–2.47), and obesity (OR=2.72; 95%CI:1.68–4.40) were significantly associated with NCD occurrence (p<0.05). These findings highlight the importance of community-based promotive and preventive interventions to reduce NCD risk factors in Mataram City.